Let Computing Be a Powerful Tool for Teaching Conceptual Biostatistics to Public Health Students - Zheng, Qi (International Journal of Advanced Corporate Learning (iJAC), 2025)
Over a decade ago some statistics educators were excited at the prospect of using computing as an effective tool for teaching conceptual knowledge of statistics, but few concrete examples of this novel teaching approach have emerged. Here I describe a novel method of treating computing as a tool for teaching conceptual biostatistical knowledge to public health students. By this new approach instructors translate the task of learning conceptual biostatistical knowledge into a process of doing carefully designed computing exercises that are reliant on elementary mathematics and first principles thinking. Infusing basic computer coding knowledge into the task of learning biostatistics, instructors succeed in bringing conceptual biostatistical knowledge into the zone of proximal development for public health students, catalyzing a beneficial synergistic effect in teaching biostatistics and computing. I demonstrate the feasibility of the new approach by citing unedited student work examples drawn from an undergraduate biostatistics course where students used the command-line R computing environment as their course software.